ANALISA PENGUJIAN EKSTRAKSI METODE SENTRIFUGAL DAN REFLUK PADA CAMPURAN AC-WC - Karisma, Candra; Sulistyono, Sonya; Badriani, Ririn Endah (FSTPT Indonesia, 2015)
Two methods for determining asphalt content that's usually used are centrifugal and reflux method. Both of The two methods have the same theoretical principle, but different ways to separate mixtures. Centrifugal method separating a mixture by stirring the solvent and sample mechanically, but the reflux method with evaporation. This study, conducted a study of two methods for bitumen extraction test, bitumen extraction comparing results between the two methods, and compare with bitumen content plans. Three levels of AC-WC (5,5%, 6,0% and 6,5%) are used for bitumen extraction. Results of studies using F-test approaches showed significant differences between bitumen extraction test results (reflux and centrifugal) against the bitumen content plan. Indicated by the value of Fcount > Ftable (38,447 > 3,555). While the results of comparison testing between centrifugal and reflux extraction using T-test indicated that there were differences in the test results, but not significantly. Where indicated tcount < ttable (0,997 < 2,4469).Bitumen extraction test results reflux method most closely with bitumen value plans and standard deviation between the smallest test results. However, testing of bitumen extraction methods reflux testing requires a very long time.